MENCIPTAKAN ORGANISASI YANG KREATIF - Purhantara, Wahyu (Jurnal Economia, 2012)
Abstract: Developing a Creative Organization. Creativity has an important meaning in organization system. In response to the always changing condition, creative steps are always taken by company/organization, such as the improvement/innovation in surveillance method, production, innovation regarding layout of offices and factories in order to be more efficient, new marketing ideas, new products creativity, or just innovating existing products, and so forth. In developing creativity organizations desperately need people who are capable of creative and analytical thinking. Creative thinking is necessary for the organization in the inception stage of each idea. When the ideas are to be implemented, organizations need peoples who have capacities of analytical thinking. Keywords: organization, creativity Abstrak: Menciptakan Organisasi yang Kreatif. Kreativitas memiliki arti penting dalam sistem organisasi. Dalam menyikapi keadaan yang berubah-ubah, langkah-langkah kreatif selalu diambil oleh perusahaan/organisasi, seperti pengembangan/ inovasi metode pengawasan, produksi, inovasi mengenai tata letak kantor dan pabrik agar lebih efisien, ide pemasaran, berkreasi dengan produk baru, atau hanya berinovasi dengan produk yang sudah ada, dan sebagainya. Dalam mengembangkan kreativitas, organisasi sangat membutuhkan orang-orang yang memiliki kemampuan berpikir kreatif dan analitis. Ketika ide-ide akan diejawantahkan, organisasi membutuhkan orang-orang yang memiliki kemampuan berpikir analitis. Kata kunci: organisasi, kreativitas